Etnogênese e afirmação étnica do Povo Tupinambá: estudo da Aldeia Muratuba no Baixo Tapajós (Santarém/Pa, 2000-2017) - SILVA, Regilene dos Santos (Universidade Federal do Oeste do Pará, 2024)
The present research aims to demonstrate the mobilization of the residents of Muratuba for the recognition of this space as an indigenous village. The research presents as a temporal cut from the years 2000 to 2017 and uses as a research method the qualitative interview based on Oral History. In the development of the work, we aim to demonstrate the sense of ethnicity that has been discussed by some scholars, as well as the debate on the concept of ethnogenesis. In what refers to the research results, we point out that the experience of the community, from the beginning of the movement to have the guarantee of recognition as a village, comes from many struggles, studies that had the contribution of anthropologists and others, but mainly, by the involvement of the community itself that aimed to clarify their origins and strive to have their rights guaranteed, preserved and respect.